Pride and Pratfalls:Recounting Embarrassing Stories Increases Creativity. Issue 1 (2nd January 2020) - Wilson, Elizabeth Ruth; Thompson, Leigh L.; Lucas, Brian J.
ABSTRACT: We explored how impression management influences creative idea generation in the design thinking process. Specifically, we examined the effect of recalling and recounting embarrassing versus prideful stories on creative idea generation. In Experiment 1, people who shared an embarrassing incident were more creative in a subsequent brainstorming task than were people who described a moment of pride. In Experiment 2, we extended this investigation to study brainstorming teams, and found that teams of senior managers who revealed an embarrassing incident generated a greater volume and variety of ideas in a subsequent group brainstorming session than did teams that shared a moment of pride. We considered the practical implications of our findings for the managers and their teams in the design thinking process.